ANALISIS PENGOLAHAN AIR TERPRODUKSI DI WATER TREATING PLANT PERUSAHAAN EKSPLOITASI MINYAK BUMI (STUDI KASUS: PT XYZ) - Andarani, Pertiwi; Rezagama, Arya (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2015)
The exploration and production process of oil and its supporting operations always generates wasteas by-product. If they are uncontrolled, it might decrease the environmental quality. Thus, it isnecessary to manage and treat the waste in order to meet the regulation standard of quality andquantity. PT XYZ is an energy company, particularly oil and gas production, which its productionactivity generate a large amount of waste as well as produced water. Thus, PT XYZ must havefacilities or produced water handling plant which could minimize pollution caused by produced water.PT XYZ already has a system of produced water handling with recycling principle. After oil and waterseparation including water treating at Water Treating Plant (WTP), produced water will be used forsteam injection. This is the part of enhanced oil recovery by steam flooding in Duri Field. Besides,produced water could be used as backwash water at WTP, that is Oil Removal Filter (ORF) and WaterSoftener, which is called brine water. If the produced water and brine water is over load the capacity ofoil enhanced recovery injection, it might be disposed through injection to Disposal Well and there arecertain condition that produced water should be discharged into canal. The objective f this study is toanalyze the performance of a water treating plant in PT XYZ. Water Treating Plant is a facility fortreating produced water. Basically, WTP is on good condition and each unit has high efficiency forseparating oil and water (60-99%). Horizontal velocity at pit #A of API Separator was larger than thedesign criteria. In addition, Water Softeners have efficiency until 99% for the hardness.